Case study the auditing department for the food service division of the Leslie Corporation - Fuentes, Fides Suzanne; Cruz, Jose Marianito; Yadao, Benedict (UP College of Engineering, 1991)
This study aimed to identify problems of the Internal Auditing Department of Leslie Corporation, specifically on the needs of the auditor for the Food Service Division. Its primary purpose was to prevent and detect fraud and anomalous transactions maximize the efficiency of the departments, thereby improve the profit-earning capacity of the corporation. The specific activities of the Food Service Auditor, along with the pertinent data needed were collected from the corporation and analysis was done, using the Stream Diagnosis and Capacity Planning. The most serious deficiencies causing more problems were derived from their application. These were: a) the employees; b) the lack of communication in decision-making between management and the department; c) the absence of advanced planning in the part of the management; d) the lack of budget for the most basic needs of the department; and e) lack of personnel in the department. Several recommendations were formed, as follows: a) scheduling of regular meetings between the management and the department; b) staff re-assignment and hiring of additional personnel; c) giving of incentives and promotions to deserving employees; d) allocation of budget to the needs of the department; e) review of procedures for cashier's remittances; f) review of job descriptions of the personnel in the department.